2014
DOI: 10.1038/labinvest.2014.110
|View full text |Cite
|
Sign up to set email alerts
|

CXCL12+ stromal cells as bone marrow niche for CD34+ hematopoietic cells and their association with disease progression in myelodysplastic syndromes

Abstract: The bone marrow microenvironment, known as 'hematopoietic stem cell niche,' is essential for the survival and maintenance of hematopoietic stem cells. Myelodysplastic syndromes (MDS) are a group of clonal hematopoietic stem cell diseases, which eventually result in leukemic transformation (acute myelogenous leukemia with myelodysplasia-related changes, AML-MRC). However, the precise components and functions of the MDS niche remain unclear. Recently, CXCL12-abundant reticular cells were shown to act as a hemato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 33 publications
(41 reference statements)
1
43
1
Order By: Relevance
“…Chondrocytes at a primary culture from articular cartilage show mature and well-formed cartilage with extracellular matrix of type-II collagen, however those with chondrocytes with a longer cultivation do not generate cartilage with type-II collagen but form fibrous tissue [16] and almost same results have been presented in chondrocytes from the costal cartilage [17]. Chondrocytes can be not only isolated from cartilage, but also differentiated from somatic stem cells including mesenchymal stem cells and marrow stromal cells [2, 20-23]. Chondrocytes have recently been generated from pluripotent stem cells like other cell types [2, 24-27].…”
Section: Discussionmentioning
confidence: 99%
“…Chondrocytes at a primary culture from articular cartilage show mature and well-formed cartilage with extracellular matrix of type-II collagen, however those with chondrocytes with a longer cultivation do not generate cartilage with type-II collagen but form fibrous tissue [16] and almost same results have been presented in chondrocytes from the costal cartilage [17]. Chondrocytes can be not only isolated from cartilage, but also differentiated from somatic stem cells including mesenchymal stem cells and marrow stromal cells [2, 20-23]. Chondrocytes have recently been generated from pluripotent stem cells like other cell types [2, 24-27].…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in the bone marrow microenvironment are also seen in myelodysplastic syndrome (MDS) and acute myeloid leukemia (AML). In MDS, in contrast to ALL, CXCL12 expression is increased . This is due, at least in part, to the expansion of CXCL12‐positive CD271 + perivascular stromal cells .…”
Section: Alterations In the Bone Marrow Microenvironment In Hematopoimentioning
confidence: 99%
“…In MDS, in contrast to ALL, CXCL12 expression is increased . This is due, at least in part, to the expansion of CXCL12‐positive CD271 + perivascular stromal cells . A recent study reported that in 38% of cases of MDS or AML, increased β‐catenin signaling and β‐catenin nuclear accumulation in osteoblasts are present .…”
Section: Alterations In the Bone Marrow Microenvironment In Hematopoimentioning
confidence: 99%
“…Cytokines and chemokines play essential roles in a number of important biological processes (Ahmed et al, 2014;Chen et al, 2018;Doring et al, 2014;Edderkaoui, 2017;Janssens et al, 2018;Ridiandries et al, 2018;Sokol and Luster, 2015;Turner et al, 2014), including hematopoiesis (Wright et al, 2002;Youn et al, 2000) and cancer metastasis (Agarwal et al, 2019;Amedei et al, 2013;Bridge et al, 2018;Chow and Luster, 2014;King et al, 2017;Marcuzzi et al, 2018;Nagarsheth et al, 2017). Because of its clearly demonstrated essential roles for hematopoiesis, CXCL12 is one of the most intensely studied CXC subfamily chemokine factor in the bone marrow (BM) niche (Abe-Suzuki et al, 2014;Aurrand-Lions and Mancini, 2018;Broxmeyer and Kim, 1999;Lewellis and Knaut, 2012;Sugiyama et al, 2006). During development, CXCL12 is essential for efficient migration of hematopoietic stem cells (HSCs) from the fetal liver, the primary hematopoietic organ during late-gestation mammalian development, to the BM, the main site of post-birth hematopoiesis (Ara et al, 2003;Christensen et al, 2004).…”
Section: Introductionmentioning
confidence: 99%